The effect of service quality and interface satisfaction on the use of technology job search website in Malaysia: The case of UUM students - Hassan, Mohamad Ghozali (2012)
Nowadays, many companies have been using their websites to share job opportunities with job seekers.This paper aims to provide further explanation about the effect of service quality (SERVQUAL) and interface satisfaction on the use of job search website in Malaysia in the case of Universiti Utara Malaysia (UUM) students.Furthermore, the conceptual framework which the researcher attempts to operate in this study includes SERVQUAL and Customer Satisfaction.More than 100 surveys in both questionnaires and online surveys were distributed to UUM final year students who have used job search website.The result of this study revealed significant relationships between SERVQUAL and interface satisfactions of job search websites.